A New Fixed Switching Frequency Direct Torque Controlled PMSM Drives with Low Ripple in Flux and Torque - Sutikno, Tole; Nik Idris, Nik Rumzi; Jidin, Auzani (ITB Journal Publisher, LPPM ITB, 2011)
Direct Torque Control (DTC) has gained popularity for development of advanced motor control due to its simplicity and offers fast instantaneous torque and flux controls. However, the conventional DTC which is based on hysteresis controller has major drawbacks, namely high torque ripple and variable inverter switching frequency. This paper presents an improved switching strategy for reducing flux and torque ripples in DTC of PMSM drives; wherein the torque hysteresis controller and the look-up table used in the conventional DTC are replaced with a constant frequency torque controller (CFTC) and an optimized look-up table, respectively. It can be shown that a constant switching frequency is established due to the use of the CFTC while the reduction of torque and flux ripples is achieved mainly because of the selection of optimized voltage vector (i.e. with an optimized look-up table). This paper also will explain the construction of DTC schemes implemented using MATLAB-Simulink blocks. Simulation results were shown that a significant reduction of flux and torque ripples which is about 90% can be achieved through the proposed DTC scheme.